Estudo de um processo alternativo de sutura da pele utilizando solda a laser - Bonifácio, Elton Diêgo (2012)
The conventional process of skin suture is used to close an incision in order to restore the form and function of the tissue after a surgical procedure. In general, special needles , surgical sutures and staples are used. Despite the advance in the materials used for suture, non-uniformity may occur in the healing process, which may cause infection and tissue damage. For this reason, health professionals seek alternatives to solve this problem. The use of laser tissue welding, in which heat sources are used, may be a promising and interesting technique. Laser welding provides advantages, when compared with conventional techniques, offers an immediate watertight closure of the incision, reduced foreign-body reaction and reduced operation times. However, due to the large number of variables, the mechanisms that act on the laser welding are not yet completely understood. It is known that laser welding is a thermally dependent phenomenon of laser energy absorption of the tissue. Consequent biothermomechanical alterations are the basis of the tissue bonding in this process. Thus, the purpose of this study is to evaluate the skin welding process by using a 808 nm diode laser. An in vitro study was proposed using pig skin to evaluate the thermal gradient, the visual aspect and the bond strength under the influence of external pressure, laser power and material addition, i.e, solder. In the present study, the bond strength of samples was evaluated by tensile tests. In addition, it was proposed a mathematical model to estimate the thermal effects on the skins by using techniques of similitude and considering parameters such as exposure time and output power of laser and position of measurement. It was also adapted an in vivo mathematical model for in vitro study in order to determine the thermal gradient and stress distribution in skin. The studies showed that incisions can be closed by using a laser source material of addition and pressure applied to edges of tissue.